On Philosophy in American Law - Mootz, Francis J (Cambridge University Press, 2013)
This project has a distinct provenance, and so it might be instructive for the reader to know this history before engaging with the lively and diverse essays in this volume. On the other hand, it is always the case that a project outstrips its humble beginnings and takes on a life of its own; this is particularly true when the project involves thirty-seven individuals. I recognize that my effort to tell the story of an undertaking such as this book is, in the end, fanciful. Nevertheless, I must give my reasons.